2015
DOI: 10.1016/j.geoderma.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption of fluorene on five tropical soils from different climes

Abstract: The main processes controlling soil-polycyclic aromatic hydrocarbon interaction is sorption-desorption as influenced by the soil physicochemical conditions. Sorption-desorption phenomena can influence translocation, persistence and bioavailability. Hence, laboratory batch experiments were undertaken to investigate the sorption characteristics of fluorene on five tropical soils from varying tropical agro-ecological zones having different physicochemical properties. Fluorene concentrations used for the study ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…This indicated that the availability of the adsorption sites for the thiram molecules reduced as the pH value increased. This finding is in accordance with the general trend observed for many various other pesticides (Liu et al, 2010;Cadkova et al, 2012;Olu-Owolabi et al, 2015). As expected, thiram is a weak acidic fungicide thus its speciation is pH dependent.…”
Section: Effect Of Ph On Adsorptionsupporting
confidence: 92%
“…This indicated that the availability of the adsorption sites for the thiram molecules reduced as the pH value increased. This finding is in accordance with the general trend observed for many various other pesticides (Liu et al, 2010;Cadkova et al, 2012;Olu-Owolabi et al, 2015). As expected, thiram is a weak acidic fungicide thus its speciation is pH dependent.…”
Section: Effect Of Ph On Adsorptionsupporting
confidence: 92%
“…Comparisons of the correlation coefficients (r 2 ) and the estimated sorption capacities (q e ) of the PFO and PSO showed that the data were better described by the PSO; the r 2 values of the PSO were close to unity and the q e values were better correlated to the experimentally obtained results. This implied that these sorptions involved sharing or exchange of valence electrons (Diagboya et al 2014a;Olu-Owolabi et al 2015).…”
Section: Cation Sorption Studymentioning
confidence: 99%
“…More recent studies, such as Boivin et al (2005) and Olu‐Owolabi et al (2014), also reported hysteresis in the desorption of organic sorbates. Olu‐Owolabi et al (2015) reported specifically adsorption–desorption hysteresis for fluorene in tropical soils, with the extent of hysteresis increasing with the soil's OM content.…”
Section: Selected Properties Of Fluorenementioning
confidence: 99%